REPLACEMENT OF THE GLASS ELECTRODE BY GRAPHITE AT ACID-BASE POTENTIOMETRIC TITRATIONS - INZELT, György; BORSOS, Katalin (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Examples are shown that the paraffin-impregnated graphite (PIGE) electrode can be used as a replacement of the fragile and expensive glass electrodes in acid-base potentiometric titration. Based on the preliminary investigations this, simple, robust and cheap electrode can be an alternative of the electrodes used in the practice at present. The open-circuit potential of the paraffin-impregnated graphite in aqueous solutions of different pHs is not sensitive to the presence of oxygen. Because of the large difference between the open-circuit potential and the pH-dependent formal potential determined by using the mid-peak potential obtained by cyclic voltammetry, it can be stated that the pH dependence is due to a surface ionic exchange process with the participation of the oxidized surface groups of carbon.